Leveraging motivation theory for research and practice with students with learning disabilities. Issue 1 (2nd January 2022) - Louick, Rebecca; Muenks, Katherine
ABSTRACT: Given that the majority of students with learning disabilities (LD) are currently educated alongside general education peers for the majority of the school day in inclusive classrooms, it behooves motivation scholars to consider the practical implications of their research for all teachers working with students with LD. The purpose of this article is to discuss how three theoretical perspectives on motivation can be leveraged to support classroom teachers' work with this student population. Following an overview of our three focus theories of motivation (goal orientation theory, self-determination theory, and expectancy-value theory), we discuss research about students with LD that employs each perspective, as well as any related interventions for students with LD. Afterwards, we provide practical implications for teachers working with students with LD. Finally, we offer recommendations for research on motivation using these and other theories that are sensitive to the specific strengths and challenges of students with LD.